Validity of Student Worksheets based Project Integrated Technological Pedagogical and Content Knowledge (TPACK) Biological Material - Wahdania Misliyanti; Ismail Ismail; Andi Munisa (Universitas Tidar, 2022)
This study aims to produce a worksheet based on an integrated TPACK project on valid Ecological material. The purpose of this study was to determine the validity of the TPACK-integrated project-based worksheet. This research is a research and development (Research and Development) with a 4D model development model consisting of four stages, namely: (1) Define, (2) Design, (3) Development, amd (4) Disseminate. The product produced in this research is the TPACK integrated project-based student worksheet, validated by 2 expert validators. The instrument used in this study was a product validation questionnaire. The data was obtained using the developed, was then analyzed quantitatively. The results showed that the level of validity of the worksheet based on the TPACK integrated project, which was 4.5, was in the valid category. So that the student worksheet based on the TPACK integrated project is declared valid. The benefit of this research is to determine the validity or level of accuracy of a basic material, namely the TPACK-based project-based worksheet so that it is useful and useful for teachers and students in the learning process.